KECERDASAN EMOSIONAL, KOMITMEN ORGANISASI, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN PT. X - Fajrin, Sekar Alvitiara; Syahrian, Syahrian (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to examine the influence of Emotional Intelligence, Organizational Commitment and Organizational Citizenship Behavior on Employee Performance. This research was conducted at PT. X, taking 78 employees as research samples using a purposive sampling techniqueThe collected data analysis system applies observation and questionnaire methods. Data analysis technique collected using multiple regression analysis. Based on the studies conducted, the results of the study show that Emotional Intelligence, Organizational Commitment and Organizational Citizenship Behavior have an influence on performance.